Spiritual Intelligence, Emotional Intelligence, Mental Health And Employee Performance In Indonesia - Hutabarat, Francis; Sitanggang, Henry; Hutabarat, Mel Susilawati (Universitas YARSI, 2023)
Spiritual intelligence, emotional intelligence, employee performance, and mental health as intervening variables are research variables and their relationship is the aim of this research. 104 respondents were obtained from purposive sampling which was used according to the research objectives. Partial Least Squares Structural Equation Modeling (PLS-SEM) with Smart-PLS 3.0 software was used in the research. Spiritual intelligence, in research results, turns out to have a positive effect on employee performance. Emotional intelligence was also found to have the same results on employee performance. Emotional intelligence is also found to have an influence on mental health. At the same time, it was found that mental health has a significant influence on employee performance. However, it was found that spiritual intelligence and mental health did not have significant results.